THE EFFECT OF INVESTMENT OPPORTUNITY SET, ACCOUNTING CONSERVATISM, MANAGERIAL OWNERSHIP, PROFITABILITY, AND DIVIDEND POLICY ON FIRM VALUE - Trisandi Eka Putri; Lolha Gantika; Icih Icih (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
This study aims to determine the effect of the investment opportunity set, accounting conservatism, managerial ownership, profitability, and dividend policy on firm value either partially or simultaneously. The data used in this study is secondary data obtained from the financial statements of all companies listed on the Indonesia Stock Exchange from 2018 to 2020 and requires closing price data published by IDX on its official website, namely www.IDX.co.id. The sampling technique used in this research is the purposive sampling technique. By using this purposive sampling technique, 167 companies were obtained which could be used as samples in this study. The data analysis technique used in this study was multiple regression analysis and hypothesis testing which was carried out using the SPSS Version 22 program. The results showed that partially the variables of the investment opportunity set, profitability, and dividend policy had a positive and significant effect on firm value. While the variables of accounting conservatism and managerial ownership have no effect on firm value. The results also show that the investment opportunity set, accounting conservatism, managerial ownership, profitability, and dividend policy variables have an effect on firm value simultaneously.